Expedient cobalt-catalyzed C–H alkynylation of (enantiopure) benzylamines - Landge, Vinod Gokulkrishna; Midya, Siba Prasad; Rana, Jagannath; Shinde, Dinesh R.; Balaraman, Ekambaram (Organic Letters, 2016)
A unified strategy for cobalt-catalyzed ortho-C-H bond alkynylation of benzylamines is reported. Simple, commercially available CoBr2 was used as a cobalt source. The developed alkynylation strategy is robust and efficient and has a broad substrate scope including 1 degrees, 2 degrees, and 3 degrees benzylamines. The mechanistic study shows that C-H bond cleavage is reversible, and the kinetic study illustrates that the rate of reaction depends solely on the catalyst.
Keywords: Terminal Alkynes; Bond Activation; Directed Functionalization; Aminoquinoline Benzamides; Ortho-C(Sp(2))-H Bonds; Mechanistic Insights; Selective Access; Carbon-Hydrogen; Nickel; Annulation